2018
DOI: 10.1097/jom.0000000000001144
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Work Productivity in Different US Occupations

Abstract: Objective:The aim of this study was to quantify the relationship between workers’ body mass index and work productivity within various occupations.Methods:Data from two administrations (2014 and 2015) of the United States (US) National Health and Wellness Survey, an Internet-based survey administered to an adult sample of the US population, were used for this study (n = 59,772). Occupation was based on the US Department of Labor's 2010 Standardized Occupation Codes. Outcomes included work productivity impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 31 publications
2
25
0
15
Order By: Relevance
“…The high prevalence of obesity among populations, especially the working forces has also put a great economic burden on governments, because the health costs of this group are high and they have more frequent absences from work [7] . In fact, obesity reduces active participation among the workers [8 ], increases absence from work, disability, and health costs [9] , which consequently leads to lower salaries [10] and reduced productivity [11] . Some studies showed that obesity caused a 13-fold higher loss of working days and an 11fold greater number of compensation claims [7,12] .…”
mentioning
confidence: 99%
“…The high prevalence of obesity among populations, especially the working forces has also put a great economic burden on governments, because the health costs of this group are high and they have more frequent absences from work [7] . In fact, obesity reduces active participation among the workers [8 ], increases absence from work, disability, and health costs [9] , which consequently leads to lower salaries [10] and reduced productivity [11] . Some studies showed that obesity caused a 13-fold higher loss of working days and an 11fold greater number of compensation claims [7,12] .…”
mentioning
confidence: 99%
“…DISCUSSÃO la que o nível de desemprego está positivamente associado ao quantitativo de cirurgias bariátricas realizadas em âmbito populacional via rede pública de saúde do Brasil 35 . Por outro lado, estudos também revelam que populações obesas tendem a apresentar menores índices de produtividade no trabalho 39,40 . Logo, combater a obesidade coletiva com métodos eficientes de tratamentos ofertados pelo sistema de saúde pública podem promover reduções significativas no custo associado a outras morbidades e promover aumento no desempenho produtivo dos indivíduos.…”
Section: Modalidadeunclassified
“…Obesity has adverse effects on quality of life (8), disability, and productivity (9), and its economic burden is borne by the patients, health care providers, insurers, and taxpayers. Using the Medical Expenditure Panel Survey, a 2015 study broke down obesity-related expenditures to 30% for Medicare and other federal sources, 11% for Medicaid, 27% for private insurance, and approximately 30% for out-of-pocket payments (10).…”
Section: Introductionmentioning
confidence: 99%